ISOLATION AND IDENTIFICATION OF SOME BACTERIA FROM COW'S MILK IN NORTHERN IRAQ - Fattah Omar , Abdul-Karim (The Iraqi Journal of Veterinary Medicine, 1996)
A total of 190 bacterial strains were isolated from both apparently healthy cows and those suffering from mastitis. The isolates were identified and classified according to their cultural, morphological, and biochemical characteristics. Staph. aureus was dominant bacterium (44.2%), being followed by E.coli (21%), P. aeruginosa (11.5%), and Strept.agalactiae (7.4)%. The Staph. aureus strains were studied most intensively, during the course of the investigation. The toxic properties of the strains were compared with other physiological properties and with their susceptibility to antibiotics. Resistance to antibiotics was slightly more widespread among the toxigenic than the nontoxigenic strains as indicated by the in vitro sensitivity test.